University language policies in Estonia and Sweden: exploring the interplay between English and national languages in higher education. Issue 1 (2nd January 2018) - Soler, Josep; Björkman, Beyza; Kuteeva, Maria
ABSTRACT: As universities seek to become more international, their need to engage with a wider range of languages, particularly English, seems more prominent. At the same time, universities are also regarded by many stakeholders as key institutions to preserve a given national language and culture. This apparent tension makes universities a fruitful ground to explore relevant issues of language policymaking. This paper analyses language policies in higher education in two northern European countries, Sweden and Estonia. Applying qualitative content analytical tools, we tackle the following questions: (1) what major themes emerge from the analysis of institutional language policy documents in Estonia and Sweden? and (2) how is English perceived in relation to other languages? Our analysis shows that, despite their different historical and sociopolitical trajectories, universities in the two countries tend to adopt similar stances vis-à-vis their language policy developments. There also exist, however, different nuances in approaching the language question, which we interpret as being the result of the particular cultural backgrounds of each country.